Pengaruh Coretax terhadap Transparansi dan Akuntabilitas Sistem Perpajakan - Muan Ridhani Panjaitan; Yuna Yuna (Jurnal Riset Akuntansi, 2024)
This study aims to analyze the impact of Coretax on the transparency and accountability of the tax system through a literature review method. Coretax, as a digital tax technology system, is expected to enhance information transparency and strengthen oversight mechanisms in tax administration. The literature review indicates that the implementation of Coretax significantly contributes to improving transparency by providing real-time access for taxpayers to tax-related information, minimizing reporting errors, and simplifying access to regulatory updates. In terms of accountability, Coretax enhances tax authorities' ability to track transaction data, reduces opportunities for manipulation, and accelerates more efficient audit processes. The findings suggest that Coretax increases public trust in a more transparent and accountable tax system. However, challenges related to digital literacy and technological infrastructure readiness need to be addressed to optimize the system's positive impact in Indonesia.